1997
DOI: 10.1046/j.1468-2982.1997.1703166.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Histamine from Dural Mast Cells by Substance P and Calcitonin Gene-Related Peptide

Abstract: The aim of the present study was to examine if the neuropeptides substance P (SP), calcitonin gene-related peptide (CGRP), neuropeptide Y (NPY) and vasoactive intestinal peptide (VIP) can stimulate histamine release from mast cells in the dura mater and thereby play a role in cranial vasoregulation and local neurogenic inflammation. Dura mater mast cells were compared with peritoneal mast cells in the rat. Histamine was released from dura mater mast cells by compound 48/80, SP and CGRP but from peritoneal mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(138 citation statements)
references
References 51 publications
4
128
2
4
Order By: Relevance
“…PGP 9.5 reactivity identifies all cutaneous nerves, 51,56 whereas only a fraction of such nerves produce CGRP. 52,56 Notably, the neuropeptide CGRP can induce degranulation of certain mast cell populations, 16,19,20 including dermal mast cells in both humans 16 and mice. 19 Accordingly, CHS in response to OX represents a setting in which mast cells contribute to the elongation of nerves that can, in turn, produce a neuropeptide with the capacity to induce functional responses in dermal mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…PGP 9.5 reactivity identifies all cutaneous nerves, 51,56 whereas only a fraction of such nerves produce CGRP. 52,56 Notably, the neuropeptide CGRP can induce degranulation of certain mast cell populations, 16,19,20 including dermal mast cells in both humans 16 and mice. 19 Accordingly, CHS in response to OX represents a setting in which mast cells contribute to the elongation of nerves that can, in turn, produce a neuropeptide with the capacity to induce functional responses in dermal mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…44 Furthermore, VIP releases a relatively small proportion (10%) of histamine from human dural mast cells, compared with CGRP (10% vs 32%). 45 Thus, it seems unlikely (although it remains to be investigated) that PACAP can induce sufficient mast cell degranulation in the perivascular space of cranial arteries to result in nociceptive input.…”
Section: The Peripheral Actions Of Pacapmentioning
confidence: 99%
“…CGRP is also implicated in modulating synaptic transmission of glutamate and acetylcholine [50][51][52]. In the periphery, release of CGRP from trigeminal fibers is believed to cause vasodilation and mast cell degranulation, ultimately resulting in a persistent pro-inflammatory sensitization of trigeminal nociceptors [53][54][55]. Studies have suggested that CGRP release works in a paracrine manner, causing excitation of nearby neuronal and satellite glial cells and stimulating its own synthesis [56].…”
Section: Functionmentioning
confidence: 99%